The relationship of some biomechanical variables to the performance of the backhand topspin stroke with accuracy for table tennis players - Jamal Gazal; Waleed Thanoon (مجلة الرافدين للعلوم الرياضية, 2023)
The study aimed to:Recognizing the values of some biomechanical variables for the backhand topspin stroke in table tennis.Recognizing the values of the accuracy test for the performance for the backhand topspin stroke in table tennis.Recognizing the relationship between a number of biomechanical variables and the accuracy values of the backhand topspin stroke in table tennis.In order to verify the objectives of the study, the researcher had assumed the following:There is a significant relationship between the values of a number of biomechanical variables and the accuracy values of the backhand topspin stroke in table tennis.    The researchers used the descriptive method for its suitability to the nature of the research, and the research sample was chosen in a deliberate way from players of Premier League clubs, the category of applicants for table tennis, which numbered (7) players representing Sulaymaniyah Sports Club and Mosul Sports Club, and registered with the Iraqi Table Tennis Federation. The researchers used scientific sources and references, content analysis, questionnaire, test and measurement, and technical scientific observation as sources for data collection. The research included biomechanical variables and the accuracy of the forehand topspin stroke.Two main experiments were conducted, The first experiment was conducted in the Sulaymaniyah Club / Sulaymaniyah Governorate, and the second was conducted in the Sports Activity Department of Nineveh Education / Nineveh Governorate. Technical scientific observation was achieved using two (2) high-speed digital cameras for the purpose of tracking the technical performance of the front screw. For biomechanical variables.    The digital film was transferred to a computer, as the variables under study were extracted by means of kinetic analysis programs (AutoCAD 2021) and the data were statistically processed using the (SPSS) program to obtain (arithmetic mean, standard deviation, coefficient of variation, and simple correlation coefficient). The researchers concluded:Accuracy is negatively affected when the center of gravity of the body is lowered in the backhand maximum swing stage of the striking arm in the backhand spin swing.Increasing the angular velocity increases the amount of accuracy in the hitting phase of the backhand spin.            Through the conclusions, the researchers recommend:Directing players to pay attention to the ideal angles for the technical performance of table tennis skills.Directing the Table Tennis Sub-Federation to provide modern training equipment to develop the technical performance of the players.Study other biomechanical variables that were not addressed in this study.